Anatomical Venous Variants in Children With Cerebral Sinovenous Thrombosis. Issue 1 (January 2019) - Kouzmitcheva, Elizabeth; Andrade, Andrea; Muthusami, Prakash; Shroff, Manohar; MacGregor, Daune L.; deVeber, Gabrielle; Dlamini, Nomazulu; Moharir, Mahendranath
Abstract : Background and Purpose—: Literature is sparse on the frequency and significance of anatomical venous variants (AVVs) in pediatric cerebral sinovenous thrombosis (CSVT). Methods—: We retrospectively reviewed children with CSVT and controls undergoing computed tomography/magnetic resonance venography from January 2008 to 2014. Clinical features examined included raised intracranial pressure, risk factors, and treatment. Radiological features examined included CSVT location, presence and type of AVVs, hemorrhagic venous infarction, and venous collateralization. Clinical outcome was measured by the pediatric stroke outcome measure and radiological outcome by thrombus recanalization. Results—: Fifty-one children with CSVT were identified. Twenty-two (43%) had AVVs at presentation. Nineteen (86%) had hypoplasia/absence of major dural sinus, 5 (23%) had persistent fetal structures, 3 (14%) had duplications/fenestrations, and 1 (5%) had disconnected superficial and deep venous systems. Controls had a slightly higher but nonsignificant prevalence 26 (51%) of AVVs. No significant clinical and radiological differences were observed between children with CSVT and AVVs compared with those with typical venous anatomy. Conclusions—: AVVs are seen in many children with and without CSVT and do not seem to alter the presentation or clinical course. The influence of these variations on the brain's ability to tolerate venous congestion because of thrombosis merits further study. Abstract : Supplemental Digital Content is available in the text.